FRI0248 Baseline Data on Patients in Giacta (Tocilizumab in Giant Cell Arteritis). (9th June 2015) - Tuckwell, K.; Collinson, N.; Klearman, M.; Dimonaco, S.; Stone, J.H.
Abstract : Background: GiACTA is a randomized, double-blind, placebo-controlled trial of an interleukin-6 receptor antagonist (tocilizumab [TCZ]) in giant cell arteritis (GCA) (ClinicalTrials.gov NCT01791153 ). 200 of the target 250 pts have been enrolled; recruitment is ongoing, making it the largest GCA trial to date. The trial hypothesis is that TCZ is effective at achieving sustained, corticosteroid (CS)-free remissions. Objectives: To report baseline characteristics of the first 200 pts enrolled and to compare characteristics of pts with new-onset GCA (n=95) to those with relapsing GCA at enrollment (n=105). Methods: Major inclusion criteria: age ≥50 y, historical ESR ≥50 mm/h or CRP ≥2.45 mg/dL, unequivocal cranial GCA symptoms or polymyalgia rheumatic (PMR), and positive temporal artery biopsy (TAB) or large-vessel imaging. The trial includes 4 arms: TCZ 162 mg SC QW plus 6-mo prednisone taper; TCZ SC 162 mg Q2W plus 6-mo prednisone taper; prednisone only, 6-mo taper; and prednisone only, 12-mo taper. Selection of the initial prednisone dose (between 20 mg/d and 60 mg/d) is at investigator discretion. The CS taper is blinded at doses <20 mg/d. Data are from a live study database and are subject to change. Results: The mean age among pts enrolled thus far is 69 y (range, 53-84); 75% are women. At entry, 95 (48%) had new-onset GCA and 105 (52%) had relapsing disease. Baseline comorbid conditions include hypertension (53%) and diabetes (12%). There have been 2 screen failures for every 5 pts enrolled. The most common reason for screen failure was insufficient evidence to support the protocol-defined diagnosis of GCA. 57% had positive TAB, and 43% were enrolled based on positive cross-sectional imaging studies. 10% had negative TAB but positive imaging study results. PMR symptoms were present in 33% of relapsing pts but only in 10% with new-onset GCA. The percentages with persistent cranial arteritis symptoms at baseline (following prednisone after initial suspicion of GCA) were 34% among new-onset pts and 44% among relapsing pts. The mean daily prednisone dose at entry for pts with new-onset GCA was 40 mg compared with 30 mg for those with relapsing disease. Although 20% of new-onset pts entered on 60 mg/d prednisone, only 4% of those with relapsing disease entered at that dose. Conversely, 36% of relapsing pts entered at the minimum daily prednisone dose – 20 mg/d – but only 12% of those with new-onset disease entered at that dose. The mean baseline BMI for pts with relapsing disease (n=102) was slightly higher than that of new-onset pts (n=92): 26.7±5.3 vs 25.1±3.9. At the time of this analysis, 54 pts (24 new onset, 30 relapsing) had received escape prednisone for disease flares. Conclusions: Demographic features of the GiACTA population reflect the characteristic epidemiologic profile of GCA. A substantial proportion of pts were enrolled based on large-vessel imaging findings rather than positive TAB. Pts with relapsing disease at entry may be more likely to have PMR at baseline and to enter at lower prednisone doses yet have higher baseline BMIs. This is likely a result of previous CS treatment. More than 25% of pts enrolled to date have received escape therapy. Therefore, if TCZ is effective as a steroid-sparing agent in GCA, the trial protocol under conduct now should have a robust ability to prove this hypothesis. Disclosure of Interest: K. Tuckwell Employee of: Roche, N. Collinson Employee of: Roche, M. Klearman Shareholder of: Roche, Employee of: Genentech, S. Dimonaco Employee of: Roche, J. Stone Grant/research support from: Roche